Analisis Pengaruh Sumber Daya Manusia Strategik Terhadap Kepuasan Kerja dan Kinerja pada Sektor Publik: Studi pada SKPD Kota Banjarmasin - Basuki Basuki; Ervica . Jamilah; Lamsah Lamsah (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
The most important of  the essential functions of human resource management is to take care of skilled  employees. The process is normally divided into two categories: first category includes  different activities such as having health and safety in working centers, performing healthy and  sport programs and some other similar activities to save and improve employees' physical  characteristics. The second group includes other important issues normally called benefit  packages, which includes good health insurance and retiring plans. Whenever an organization  provides good benefit package and supporting programs, there is a better job satisfaction among  employee. This study try to find out about, the effects of related services to support employee to reach job  satisfaction and employee activities in public sectors called SKPD in Banjarmasin City is  used 86 random samples. The results show that employees are relatively satisfied from the  benefit package of the SKPD and they were relatively happy on working for such organization.